Marketing Strategy Analysis and SWOT Analysis of HeyTea - Jia, Zhiyu; Zhang, Yaolin (Transactions on Social Science, Education and Humanities Research, 2024)
In modern society, new tea brands have garnered significant attention and affection. HeyTea is one of the more popular hot drink shops and has been very popular with consumers since it opened. This paper will also analyze the competitive strategy of Hicha in China. HeyTea’s sales strategy and advantages will be analyzed. This article analyzes the store’s advantages, marketing mode, and other aspects. The SWOT model is used to analyze the strengths, weaknesses, opportunities, and risks of HeyTea stores, evaluate Hicha’s sales strategy, and assess how Hicha leverages its advantages among emerging tea beverage brands to attract more consumers. Based on the marketing strategy of the well-known Internet brand HeyTea, this paper analyzes its effectiveness in attracting the target audience and enhancing brand awareness. Based on the above analysis, this article proposes improvement suggestions from aspects such as product innovation and social media marketing. It also includes a vision for the future.